Conjugate heat transfer in channels with heat-conducting inclined fins - Perao L.H.* (2018)
© 2018 Taylor & Francis.Conjugate heat transfer in a finned channel with equally spaced fins placed transversely to the flow direction following in-line and staggered arrangements is evaluated. The fins and channel walls are heat-conducting and are fully coupled to a turbulent fluid flow problem. The hydrodynamic and thermal effects of the fin blockage ratio, fin angle, and flow velocity were investigated. The simulations show that the fin arrangement is of paramount importance on the performance of the heat exchanger: the staggered fin configuration provided lower pressure drop and higher heat transfer rate than the in-line fin arrangement for different flow conditions.